MAKNA TARI SIKAMBANG PADA MASYARAKAT KAMBANG KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Vani Sasri Wahyuni; Nursyirwan Nursyirwan; Rosta Minawati (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT This writing discusses the meaning of Sikambang dance in Lengayang sub-district, Pesisir Selatan district, and West Sumatera province. Sikambang dance is inspired by the story of king’s family in Kambang region. Sikambang dance functions as entertainment. Sikambang dance consists of three interconnected acts that narrate about the story of king’s family. Those acts consist of Sikambang act, Maratok act, and Katera act. Sikambang dance also has meaning explained or conveyed through movement, dancer, music, costume plus make-up, floor pattern, property, and performance stage. Keywords: Sikambang dance, Maratok, Katera, Meaning